Ecotoxicological assessment of the potential impact on soil porewater, surface and groundwater from the use of organic wastes as soil amendments - Alvarenga, Paula (2017)
This study aimed to assess the potential impact on soil porewater, surface and groundwater from the beneficial application of organic wastes to soil, using their eluates and acute bioassays with aquatic organisms and plants: luminescence inhibition of Vibrio fischeri (15 and 30 min), Daphnia magna immobilization (48 h), Thamnocephalus platyurus survival (24 h), and seed germination of Lolium perenne (7 d) and Lactuca sativa (5 d). Some organic wastes' eluates promoted high toxic responses, but that toxicity could not be predicted by their chemical characterization, which is compulsory by regulatory documents. In fact, when organisms were exposed to the water-extractable chemical compounds of the organic wastes, the toxic responses were mare connected to the degree of stabilization of the organic wastes, or to the treatment used to achieve that stabilization, than to their contaminant load. That is why the environmental risk assessment of the use of organic wastes as soil amendments should integrate bioassays with eluates, in order to correctly evaluate the effects of the most bioavailable fraction of all the chemical compounds, which can be difficult to predict from the characterization required in regulatory documents. According to our results, some rapid and standardized acute bioassays can be suggested to integrate a Tier 1 ecotoxicological evaluation of organic wastes with potential to be land applied, namely luminescence inhibition of V fischeri, D. magna immobilization, and the germination of L. perenne and L sativa.